Growth and Treatment Performance of Three Macrophytes in a Pilot-Scale Horizontal Subsurface Flow Constructed Wetland for Slaughterhouse Wastewater - , Nelson Mbanefo Okoye; , Chimaobi Nnaemeka Madubuike; , Ifeanyi Uba Nwuba; , Louis Chukwuemeka Orakwe (Archives of Current Research International, 2018)
Slaughterhouse wastewater in Nigeria poses a risk to public health due to lack of treatment as the conventional treatment plants have proven non-sustainable. Constructed wetlands (CW) have emerged as an efficient technology for treatment of wastewater in developing countries because of its low cost, ease of operation/maintenance and good performance. The feasibility of using CW to remove pollutants from slaughterhouse wastewater was tested using three macrophytes; Thalia geniculata, Colocasia esculenta and Typha latifolia. The result showed that all macrophytes tolerated of the tested conditions. The BOD, TSS, NH3-N, NO3-N and PO43- of slaughterhouse effluent reduced after treatment in all cells. There was a higher removal of most pollutants in planted than in unplanted cells. The Thalia geniculata cell outperformed the others for TSS and NH3-N, while Typha latifolia cell had a higher removal rate for BOD and PO43-. In conclusion, Thalia geniculata is a more suitable plant to treat slaughterhouse wastewater because of its higher above ground biomass yield.